SCIENCE OF THE 21ST CENTURY: FUNDAMENTAL OR APPLIED SCIENCE (OR TECHNO-SCIENCE)? - V. P. Kotenko (Дискурс)
The article is devoted to science of the 21st century. The author analyses characteristics of science of the 21st century and the concept of "fundamental" and "applied" science. Regularities of the development of fundamental and applied sciences are determined. The author gives differentiation of fundamental and applied sciences on the basis of the carried out research work.